Evolutionary stages of IFAC managerial accounting that prevail in a furniture industrial pole - DOI: http://dx.doi.org/10.16930/2237-7662/rccc.v15n45p9-22 - Macohon, Edson Roberto (2016)
The International Federations of Accountants (IFAC) has identified four stages of progressive managerial accounting. This study aims at investigating the evolutionary stages of managerial accounting that prevail in a furniture industrial pole. For this, a descriptive research was carried out from a survey, having as population 73 industries associated with the Union of Industries and Construction of Furniture of São Bento do Sul, SC, Brazil, and a non-probability sample of 15 industries. The survey results have shown that the artifacts of managerial accounting that got more than 60% of indications, such as project implemented are: simulations of profitability of products; cost of products by cost absorption; monitoring the evolution of non-financial indicators; economic-financial index, such as Return of Investment (ROI), Return on Equity (ROE) and index of liquidity; cost reduction during the design phase of new product; spreadsheets of logistic costs. The artifacts that had a percentage above 60% of indications such as a non-implemented project are:  Activity Based Costing (ABC); reports generation by Business Intelligence (BI); Balanced Scorecard (BSC); Economic Value Added (EVA ); transfer pricing; and Just-in-time (JIT).